RETRACTED ARTICLE: Role of oxidative stress in Retinitis pigmentosa: new involved pathways by an RNA-Seq analysis. Issue 1 (2nd January 2019) - Donato, Luigi; Scimone, Concetta; Nicocia, Giacomo; D'Angelo, Rosalia; Sidoti, Antonina
Statement of Retraction: We, the Editor[s] and Publisher of Cell Cycle, have retracted the following article: Role of oxidative stress in Retinitis pigmentosa: new involved pathways by an RNA-Seq analysis Luigi Donato, Concetta Scimone, Giacomo Nicocia, Rosalia D'Angelo & Antonina Sidoti Pages 84-104 | https://doi.org/10.1080/15384101.2018.1558873 The above article has been retracted as a result of concerns regarding the use of raw data by one of the authors upon which the presented research has been based. After examination and approval from the author concerned, the consensus is that the data was used without consent, and that therefore the article must be retracted. We note that we received, peer-reviewed, accepted, and published the article in good faith based on the purported veracity of these representations and warranties. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".